Imaginários sobre a língua nas narrativas jornalísticas da revista Veja - Nascimento, Bruno Ribeiro (2014)
The objective of this study is to analyze the imaginary manifestations about the language in texts published by Veja magazine between 2000-2012. Nine images about language and two canonical narratives were identified and characterized that cross the publication during this period of 12 years and analyzed how they dialogue with the symbolic and mythic dimension of the news. Covered up all the magazine content, making no distinction between the various journalistic genres of texts analyzed. The corpus has 16 reports, two boxing texts and three interviews which is subject any topic related to human language. In total, has 21 published texts. The selection of materials was qualitative in nature. The research technique used to identify how the imaginary about the language is manifested in Veja was mitocrítica, which aims to infer from cultural manifestations of a society which are the directors myths behind these productions. The approach adopted in this work is phenomenological, describing the symbolic forms of journalistic narratives. This research is descriptive, the document type. It is emphasized as from the General Gilbert Durand Imaginary Theory, as the myths are shown specifically in the texts on the language of Veja magazine as from a dialogue between real and dream, universal and particle, where the imaginary capacity sapiens is filled with historical, social and cultural moments present in the publication, creating their own symbols and mythologies. The theoretical assumption adopted was symbolic work of news (MOTTA, 2006), stating that the texts reported daily by the journalistic media are not just reflections of everyday life, or a representation of the world, but perform an aesthetic experience, factual and diegetic , thus producing the "narrative effect" in the news and press reports. As a result of the study was possible to see how the journalistic narratives about human language published by See, as a holder of symbolic systems that reconstruct reality, not just report facts, events and everyday episodes, but also resort to symbolic meanings, myths and archetypes that are far beyond 'pure and simple information'.